Sensitization evaluation of the AISI 2205 duplex stainless steel by the IQ value in EBSD technique. (November 2019) - Jinlong, Lv; Zhuqing, Wang
Abstract: The degree of sensitization of the 2205 duplex stainless steel was evaluated by the double loop electrochemical potentiokinetic reactivation technique and EBSD method. The IQ value of ferritic phase was higher than that of austenitic phase for solid solution 2205 duplex stainless steel. However, some local small regions in ferritic phase and grain boundaries showed very low IQ value for sensitized 2205 duplex stainless steel, which was attributed to the precipitation of carbides and the formation of chromium depleted regions. This conclusion was supported by electrochemical results. Therefore, the IQ value could evaluate the degree of sensitization of the duplex stainless steel. Highlights: IQ value in EBSD was used to evaluate the sensitization of 2205 duplex stainless steel. The IQ value of ferritic phase was higher than that of austenitic phase. Local regions in ferritic phase and boundaries showed low IQ value due to precipitated phase.